Risk Factors for Arterial Ischemic Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Risk factors in 212 children (54% male; median age 5 years) presenting with a first arterial ischemic stroke (AIS) over 22 years were studied at Great Ormond Street Hospital for Children, London, UK.